Studying the Interaction between a New Mixture in Enhancing Drag Reduction Efficiency - Abdulbari, Hayder A.; Faraj, Emsalem (IACSIT Press, 2015)
Polymers are used as drag reducer in a strategic pipeline successfully for the past few decades due to its viscoelastic properties that can suppress the turbulent in pipelines. One of the many issues facing the use of these additives is its resistance to high shear forces during the transportation where it can be easily degraded where they pass them a pump. In the present work, polymer-surfactant complexes of anionic polymer and nonionic surfactant are investigated to prove its capability in enhancing the drag reduction and mechanism degradation performance. The interaction between anionic polymer Poly (acrylamide-codiallyl-dimethylammonium chloride) and nonionic surfactant tween 20 in aqueous solution has been studied by using rheology, rotating disk apparatus (RDA) and pipe loop techniques. The effect of polymer concentration, surfactant concentration and rotational speed in enhancing the drag reduction were studied. The results showed that almost 35% drag reduction can be obtained. In addition, the effect of the degradation on the mixtures as a function in the time has been discussed also.